2019
DOI: 10.1186/s12944-019-1117-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimating fetal cholesterol synthesis rates by cord blood analysis in intrauterine growth restriction and normally grown fetuses

Abstract: BackgroundCholesterol is an essential component in human development. In fetuses affected by intrauterine growth restriction (IUGR), fetal blood cholesterol levels are low. Whether this is the result of a reduced materno-fetal cholesterol transport, or due to low fetal de novo synthesis rates, remains a matter of debate. By analyzing cholesterol interbolites and plant sterols we aimed at deeper insights into transplacental cholesterol transport and fetal cholesterol handling in IUGR with potential targets for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Although the cause of the low fetal HDL concentration in neonates with IUGR is still a matter of debate, it was suggested that HDL is the result of diminished fetal de novo synthesis. 37 In the present study, HDL significantly increased in omega 3 treated neonates compared to the control group, which agreed with the results of El-alkamy et al 33 and Mohamed et al 38 studies. This witnessed effect might be attributed to that Omega 3 PUFAs, especially DHA, increase HDL-C. 39 The formation of HDL is related to the catabolism of TG-rich lipoproteins such as VLDL or intermediate-density lipoprotein (IDL) by LPL.…”
Section: Discussionsupporting
confidence: 93%
“…Although the cause of the low fetal HDL concentration in neonates with IUGR is still a matter of debate, it was suggested that HDL is the result of diminished fetal de novo synthesis. 37 In the present study, HDL significantly increased in omega 3 treated neonates compared to the control group, which agreed with the results of El-alkamy et al 33 and Mohamed et al 38 studies. This witnessed effect might be attributed to that Omega 3 PUFAs, especially DHA, increase HDL-C. 39 The formation of HDL is related to the catabolism of TG-rich lipoproteins such as VLDL or intermediate-density lipoprotein (IDL) by LPL.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, even though cholesterol synthesis/absorption ratio was rising as pregnancies advanced in both groups, the pattern of simultaneous changes in these processes was somewhat different among GDM and non-GDM subjects, especially when it comes to cholesterol absorption. Previous analyses have pointed towards the absorption markers as indicators of maternal–fetal cholesterol transport as well [ 33 , 34 ], demonstrating lower levels of plant sterols in umbilical cord blood of neonates with intrauterine growth restriction [ 35 ]. Herein, we demonstrated lower levels of cholesterol absorption in mothers with GDM, which might suggest decreased fetal supply by cholesterol, even though endogenous cholesterol synthesis was elevated.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is important to highlight the importance of cholesterol homeostasis in fetal development [ 59 ]. Cholesterol is an essential nutrient for fetal growth.…”
Section: Discussionmentioning
confidence: 99%